Media Pembelajaran Flipbook Berbasis Flip PDF Pada Pembelajaran Matematika: Systematic Literature Review - Moniko Triharjo; Reny Wahyuni; Idul Adha (Proceeding of Silampari Conference of Life Science and Technology, 2026)
Background: With the advancement of technology today, teachers are required to be able to utilize various media. Educators only use blackboards, books, worksheets, and regular PowerPoint slides as learning media, and students only listen to what the educators explain. This causes boredom and monotonous learning, making students uninterested in the learning process. One solution is the presence of interactive media alternatives to make learning more interesting and facilitate students. Professional flip PDF-based e-books are one alternative media that can be used by both educators and students. Objective: This study aims to evaluate the effectiveness of using Flipbook learning media based on Flip PDF Corporate in mathematics learning, particularly to improve students' conceptual understanding, learning independence, and problem-solving skills. Method: The method used is a systematic literature review (SLR), by examining various previous studies relevant to the application of Flipbook in mathematics learning. Review: The research results indicate that the use of this media is effective in enhancing mathematical concept understanding, as the multimedia elements in the Flipbook help students grasp abstract concepts. In addition, the use of e-modules based on Flip PDF Corporate increasing students' learning independence and interest in learning, as well as problem-based learning models (PjBL) in Flipbooks contributing positively to students' mathematical problem-solving skills. Conclusion: This study concludes that Flipbook-based media can improve the quality of mathematics learning, provide a more interactive learning experience, and develop students' critical thinking and problem-solving skills. For further research, it is recommended to implement it in classes with a larger sample and to test the application of this media on various mathematics materials.